Helicobacter pylori infection is associated with gallstones: Epidemiological survey in China - Zhang, Fen-Ming (World J Gastroenterol, 2015)
AIM: To elucidate the prevalence and risk factors for gallstones, primarily focusing on Helicobacter pylori (H. pylori) infection. METHODS: A total of 10016 Chinese subjects, who had undergone physical examination, fasting (13)C urea breath test and abdominal ultrasonography, had sufficient blood test data, and had finished a questionnaire, were included in this cross-sectional study. Participants (n = 1122) who had previous eradication of H. pylori were studied separately. RESULTS: Gallstones were discovered in 9.10% of men and 8.58% of women, with no significant sex difference. Multivariate analyses displayed that age, aspartate aminotransferase, total cholesterol, H. pylori infection, hepatitis C virus (HCV) infection, and fatty liver had a significant association with gallstones (P < 0.05). Successive multiple logistic regression analysis including index of odds ratio (OR) and standardized coefficient (β) indicated that older age (OR/β = 1.056/0.055), H. pylori infection (OR/β = 1.454/0.109), HCV infection (OR/β = 1.871/0.123), and fatty liver (OR/β = 1.947/0.189) had a significant positive association with gallstones. After age stratification, H. pylori infection and fatty liver still had a significant positive association with gallstones in any age-specific groups, whereas HCV infection had a significant positive association in patients aged > 40 years. The prevalence of gallstones among H. pylori-positive, H. pylori-eradicated, and H. pylori-negative subjects was 9.47%, 9.02%, and 8.46%, respectively. The matched analysis showed that gallstones among H. pylori eradicated subjects was significantly lower compared with H. pylori-positive subjects (P < 0.05). CONCLUSION: H. pylori infection and fatty liver have a significant positive association with gallstones. H. pylori eradication may lead to prevention of gallstones.